Representasi Lima Tahapan Kesedihan (Five Stages of Grief) dalam Film “172 Days” (Universitas Palangka Raya, 2026)
This study aims to analyze the representation of the five stages of grief in the film 172 Days through a literary psychology analysis. This film is of particular interest because it is an Indonesian box office hit based on a true story that portrays both emotional and religious experiences of loss. The study employs a qualitative descriptive approach, with the objects of analysis being visual scenes and the dialogue of the character Zira that represent the experience of grief. Data were collected through systematic observation of the film and a review of relevant literature on grief theory. Data analysis was conducted using content analysis techniques, classifying scenes based on the stages of grief according to Elisabeth Kübler-Ross: denial, bargaining, anger, depression, and acceptance. The results indicate that the film represents the five stages of grief progressively through the main character’s emotional journey. The denial stage is evident through the denial of the illness’s condition; bargaining through prayer as a form of spiritual negotiation; anger through emotional outbursts following the loss; depression through deep sorrow and attachment to memories; and acceptance through embracing the loss and finding new meaning in life. These findings indicate that the film functions not only as a medium of entertainment but also as a psychological representation of the grieving process that is universal and reflective for the audience.